Thermoregulatory responses during road races in hot-humid conditions at the 2019 Athletics World Championships - Polly Aylwin (12302435) (2023)
This paper provides a kinetic observation of both core and skin temperatures in 108 elite athletes, during various outdoor competition events, adding to the very limited data so far available in the literature taken during elite competitions. The field skin temperature findings contrast previous laboratory findings, likely due to differences in relative air velocity and its impact on the evaporation of sweat. The rapid rise in skin temperature following cessation of exercise highlights the importance of infrared thermography measurements being taken during motion, not during breaks, when being used as a measurement of skin temperature during exercise. Other Information Published in: Journal of Applied Physiology License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1152/japplphysiol.00348.2022